DEVELOPMENT OF A FUNCTIONAL COMPOSITION OF PLANT RAW MATERIALS - Lunina, Ludmila; Tazova, Zareta; Siyukhov, Hazret; Skhalyakhov, Anzaur (Revista Inclusiones, 2020)
Designing compositions of plant materials intended for enriching food products is a rather laborious process; creating a prescription formula may take a long time, which is due to many different options that cannot be measured with a finite number. Therefore, when developing a functional composition of plant raw materials, the authors used the method for planning experiments to compose mixtures. Using the Designs for Constrained Surfaces and Mixtures procedure of the Design of Experiments module of the STATISTICA 10 software suite, a design of the experiments has been made, studies have been performed for determining the quantitative content of functional ingredients in the test samples, the results have been mathematically processed, a scientifically substantiated optimal component composition has been obtained for two variants of plant raw materials composition with the following component ratio, % wt.: variant 1: leaves of stinging nettle — 15, herb of echinacea purpurea — 15, inflorescences of red clover — 40, and rosehips — 30; variant 2: leaves of stinging nettle — 25, herb of echinacea purpurea — 25, inflorescences of red clover — 30, and rosehips — 20. It has been experimentally found that in the composition of the first variant, the content of vitamin E is 17.769 mg of tochopherol equivalent/100 g, which is 1.2 times higher than the recommended daily consumption, and in the second variant, the content of calcium is 640.36 mg/100 g or 53.4 % of the recommended daily consumption, which allows attributing the developed composition variants of plant material to functional products.